Monetary transmission: empirical evidence from Luxembourg firm level data - Patrick Lünnemann; Thomas Y. Mathä (European Central Bank (ECB), 2001)
This paper investigates the transmission of monetary policy using data from a panel of Luxembourg firms. The results indicate that the sales accelerator may be at work. A very robust result is the negative effect of the user cost of capital on firms' investment ratio. Changes in user costs are significantly affected by changes in the monetary policy indicator. In addition, firm specific balance sheet characteristics, such as the lagged cash stock to capital ratio influence the investment behaviour according to the broad credit channel theory. Using various sample splits, it is shown that young firms, in particular, are more sensitive to user cost changes, sales growth and the lagged cash to capital ratio.
Keywords: D21; D92; E22; E52; 330; credit channel; Investment; panel data; user cost of capital